Road traffic accident victims socio-demographic profiles: a community based study in Central India - Gharde, Pramita Muntode; Quazi, Syyed Zahiruddin; Wagh, Vasant V. (International Journal Of Community Medicine And Public Health, 2017)
Background: A road traffic injury is any injury caused due to crashes originating, terminating or involving a vehicle partially or fully on a public highway.The road crashes are unlike communicable diseases where the role of agent, host and environment is more defined. The aim and objective was to study of the socio-demographic profile of victims of road traffic accidents. Methods: A community based cross-sectional study was conducted from November 2010 to September 2012 in 3 blocks of Wardha district, in Central India. The sample size was estimated using purposive sampling technique. The data was analyzed using EPI-Info version 3.5.4. Results: Out of 385 study subjects, maximum victims were in 30-60 years age group, 320 were males and 16.88% i.e. 65 were females. The total numbers of literate victims were 94.80%. Maximum accidents were seen in victims who were employed in service 151 (39.22%), followed by self employed 27%. Conclusions: Maximum victims were in 30-60 years age group which is the productive age group and male dominance was also observed which means loss of work days leading to loss of wages and loss of family income hence directly affecting the family economy.